1991
DOI: 10.1161/01.cir.83.6.1976
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic angioplasty in totally occluded peripheral arteries. Initial clinical, histological, and angiographic results.

Abstract: Ultrasonic angioplasty may be a useful clinical method for recanalization of total occlusions in patients with peripheral vascular disease. Ultrasonic energy appears to cause controlled injury to the atherosclerotic intima by selectively disrupting the ultrasound-sensitive occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
3

Year Published

1992
1992
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(28 citation statements)
references
References 19 publications
1
24
0
3
Order By: Relevance
“…Activation of the wire can disrupt the thrombus within minutes into particles which can either be aspirated or embolized distally. Percutaneous, transvascular ultrasonic disruption of a femoral artery thrombus has been reported in a single patient ( 13), and ultrasound has also been used to recanalize arteries obstructed by atherosclerosis ( 19,20). In general, few complications have been reported in dog models, although heating ofthe catheter may occur ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the wire can disrupt the thrombus within minutes into particles which can either be aspirated or embolized distally. Percutaneous, transvascular ultrasonic disruption of a femoral artery thrombus has been reported in a single patient ( 13), and ultrasound has also been used to recanalize arteries obstructed by atherosclerosis ( 19,20). In general, few complications have been reported in dog models, although heating ofthe catheter may occur ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…12,16,36 It is generally accepted that clot lysis depends on inertial cavitation, where microbubbles expand rapidly and collapse violently with the resultant mechanical force causing clot lysis. 15,24,[45][46][47][48] Lower-frequency systems (230-kHz ExAblate transducer) can use cavitation for treatment effect while mid-frequency (650-kHz) or high-frequency (1-MHz) systems are more ideal for creating a precise thermal lesion with the avoidance of cavitation.…”
Section: Sonothrombolysismentioning
confidence: 99%
“…Previous reports have shown that US can accelerate fibrinolysis in vivo, but they differ from our findings in several respects. In some reports, thrombi were mechanically disrupted in vitro 22,23 or in animal models 23,24 with wires vibrating at US frequencies in the absence of plasminogen activator, and this approach has been tested in small studies in patients with coronary 25 or peripheral 26,27 arterial occlusion and with occluded coronary bypass grafts. 28 This treatment requires endovascular positioning of the wire, and it can result in vessel wall damage, excessive heating, and distal embolization of clot fragments.…”
Section: Suchkova Et Al Ultrasound Increases Thrombolysis and Perfusionmentioning
confidence: 99%